Since both equations give the value of "y", we can set them equal to each other and solve for "x":
8x + 32 = -8x
Adding 8x to both sides:
16x + 32 = 0
Subtracting 32 from both sides:
16x = -32
Dividing by 16:
x = -2
Now that we have found the value of "x", we can substitute it back into either of the original equations to find the value of "y". Using y = 8x + 32:
y = 8(-2) + 32
y = -16 + 32
y = 16
Therefore, the solution to the system of equations is x = -2 and y = 16.
Solve the system by substitution.
y, equals, 8, x, plus, 32
y=
8x+32
y, equals, minus, 8, x
y=
−8x
1 answer